1997
DOI: 10.2337/diab.46.5.742
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Stimulates Nitric Oxide Synthesis in Human Platelets and, Through Nitric Oxide, Increases Platelet Concentrations of Both Guanosine-3′, 5′-Cyclic Monophosphate and Adenosine-3′, 5′-Cyclic Monophosphate

Abstract: The insulin-induced platelet anti-aggregating effect is attributed to a nitric oxide (NO)-mediated increase of cyclic guanosine monophosphate (cGMP). The aim of this work, carried out in human platelets, is to show whether insulin increases NO synthesis in platelets and whether it enhances not only cGMP but also cyclic adenosine monophosphate (cAMP) in these cells. We observed that 1) insulin dose-dependently increases NO production, evaluated as citrulline synthesis from L-arginine (n = 4, P = 0.015); 2) insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 0 publications
4
64
0
1
Order By: Relevance
“…Trovati et al (24) reported earlier that platelets suspended in plasma are inhibited by insulin through a rise in [cAMP]. Also cAMP production induced by the stable PGI 2 analogue iloprost and the adenylyl cyclase activator forskolin was enhanced by insulin.…”
Section: ؉mentioning
confidence: 93%
“…Trovati et al (24) reported earlier that platelets suspended in plasma are inhibited by insulin through a rise in [cAMP]. Also cAMP production induced by the stable PGI 2 analogue iloprost and the adenylyl cyclase activator forskolin was enhanced by insulin.…”
Section: ؉mentioning
confidence: 93%
“…Furthermore, not only was NO capable of activating tyrosine kinase or PI 3-kinase but also the "messenger" NO could activate NOS in the absence of either tyrosine kinase or PI 3-kinase (or both) in the NOS system (unpublished results), whereby NO would probably amplify its own generation by "feedback" activation of NOS and, consequently, would amplify the effect of insulin itself in the system. It has been reported previously that NO can stimulate glucose metabolism in tissues (25) and that insulin treatment of platelets, cells that do not require insulin for glucose metabolism, results in the increased production of NO (26). However, it has not been previously appreciated that the production of NO as a result of the activation of NOS by insulin is actually an essential step-beyond the activation of both PI 3-and tyrosine kinases by insulin-in the transduction of messages that affect glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…We measured the effects of insulin on cGMP and cAMP in platelets at close intervals ranging from a few seconds to 120 min to show that insulin action on both nucleotides is very rapid, reaching the maximum effect after only 2 min [13]. Furthermore, we observed that in these cells insulin increases NO production in a few minutes [13].…”
Section: : 831±839]mentioning
confidence: 99%
“…We recently showed in both human VSMC (hVSMC) and in platelets that insulin increases intracellular concentrations of cGMP [8±13], by a mechanism which is blocked both by the guanylate cyclase inhibitor methylene blue and by the NOS inhibitor l-NMMA [8,9,12,13]. We also showed that insulin can, in both hVSMC and platelets, increase the intracellular concentrations of adenosine 3':5'-cyclic monophosphate (cAMP), with a mechanism blocked by l-NMMA [9,13], that could be attributed to cGMP [14±17] or directly to NO [18] as we will explain more extensively in the Discussion.…”
Section: : 831±839]mentioning
confidence: 99%